STRATEGI PENGELOLAAN KEUANGAN DAN PENINGKATAN PENDAPATAN USAHA NELAYAN DI DUSUN KOKO, DESA TANJUNG LUAR LOTIM - M Kholil Al Farisi; Triana Lidona Aprilani; Dara Nida Utamie; Baiq Dewi Lita Andiana (Yayasan Nusantara Hasana Berdikari, 2026)
This study aims to analyze the current financial management practices of fishermen in Dusun Koko, Tanjung Luar Village, East Lombok, and to formulate effective strategies for improving their economic stability and income. The research employed a qualitative approach with a case study design, involving five fishermen as the main informants. Data were collected through in-depth interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that most fishermen still manage their finances in a traditional manner without structured recordkeeping, causing fluctuating and seasonal income to be spent primarily on daily consumption without allocation for savings, investment, or emergency funds. Recommended strategies include implementing the 5-3-2 income allocation system, adopting simple financial recordkeeping, establishing emergency funds, conducting financial literacy training involving fishermen’s wives, and diversifying businesses through seafood processing and non-fishing side enterprises. Applying these strategies is expected to increase income by up to 20% during lean fishing seasons, strengthen economic resilience, and promote sustainable financial independence among fishermen.